Community, Public Archaeology, and Co-construction of Knowledge Through the Educational Project of a Rural Mountain School - Fernández Mier Margarita; López Gómez Pablo; Sánchez-Broch Paloma; Carballido González Elías (Open Archaeology)
In recent decades, rural societies have been forced to face major transformations in the context of globalization. Social and economic changes, such as the disappearance of traditional economic bases or the severe process of depopulation and exodus towards urban spaces and, in turn, the aging of the persistent population in rural areas, have been translated into a dynamic of disarticulation that has also affected identities and has brought into question the survival of cultural elements with a long historical diachrony. This context has stimulated the research that different scholars carry out trying to understand the rural world from a complex and multifaceted perspective, but it has also served to draw attention to the need to generate forms of research and knowledge creation more connected to the communities. In this article, we present our experience through the project ConCiencia Histórica, a proposal that we have developed with a school located in a mountain area in northern Spain that uses project-based education and STEAM methodologies and in which we followed our historical and archaeological research in this area as a common thread in its educational programming.